ANALISIS REAKSI PASAR TERHADAP PENGUMUMAN STOCK REPURCHASE - INDAH SUNARINGTYAS, NOVI (Jurnal Ilmu Manajemen (JIM), 2014)
Abstract: The purpose of this research was to analyze the impact of stock repurchase announcement in stock market. The observation was done in seven days, consist of three days before announcement, announcement day and three days after stock repurchase announcement. Statistical experimental use paired sample t-test. The result of this research shows that before stock repurchase announcement and after stock repurchase announcement no difference reaction that show by abnormal return and trading volume activity. Keywords: stock repurchase announcement, abnormal return, and trading volume activity.